COMPARATIVE ANALYSIS OF SURFACE ATMOSPHERIC PARAMETERS BETWEEN SURABAYA AND SIDOARJO - Purnama, Fahmi Yuwan; Nurjani, Muhammad Abil (Jurnal Segara, 2024)
Geographical location and topography determine the characteristics of atmospheric parameters in a location. Surabaya has a geographical and topographical location that is different from Sidoarjo, especially Surabaya to the north has a natural barrier in the form of Madura Island. This study aims to prove the difference in the character of atmospheric parameters between Surabaya and Sidoarjo. This study used the Windrose method and an average comparison, the data used in this study were Ogimet data from 2 Observation Stations, namely Djuanda Meteorological Station and Tanjung Perak. The results of this study show that the direction of arrival of the wind is dominant from the east direction for the Stamet Djuanda region while for the Tanjung Perak Stamet the wind is dominated from the Southeast direction, the area affected by land and sea winds is the Stamet Djuanda area where the sea breeze starts at 18.00-00.00 and for onshore wind starts at 03.00-09.00 while for Stamet Tanjung Perak has no effect due to the barrier, namely Madura Island. Based on the average comparison method, different values of temperature, humidity and precipitation parameters were obtained, indicating the influence of georaphysical and topographic locations of the 2 research areas.